2019
DOI: 10.1155/2019/3462530
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Activates the NLRP3 Inflammasome: A Novel Mechanism of Atherosclerosis

Abstract: The endoplasmic reticulum (ER) is an important organelle that regulates several fundamental cellular processes, and ER dysfunction has implications for many intracellular events. The nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome is an intracellularly produced macromolecular complex that can trigger pyroptosis and inflammation, and its activation is induced by a variety of signals. ER stress has been found to affect NLRP3 inflammasome activation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 220 publications
(257 reference statements)
2
71
0
1
Order By: Relevance
“…In acute injuries, inflammation restores tissue homeostasis but prolonged inflammatory conditions stimulate the immunosuppressive network in an attempt to prevent excessive inflammatory damage in tissues (see below). There is clear evidence that ER stress can elicit inflammatory responses in many age-related diseases, e.g., atherosclerosis [72], hepatic steatosis [73], and age-related macular degeneration [74]. It seems that the activation of inflammasomes is involved in the crosstalk between ER stress and inflammatory responses in some diseases [72,73].…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In acute injuries, inflammation restores tissue homeostasis but prolonged inflammatory conditions stimulate the immunosuppressive network in an attempt to prevent excessive inflammatory damage in tissues (see below). There is clear evidence that ER stress can elicit inflammatory responses in many age-related diseases, e.g., atherosclerosis [72], hepatic steatosis [73], and age-related macular degeneration [74]. It seems that the activation of inflammasomes is involved in the crosstalk between ER stress and inflammatory responses in some diseases [72,73].…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
“…There is clear evidence that ER stress can elicit inflammatory responses in many age-related diseases, e.g., atherosclerosis [72], hepatic steatosis [73], and age-related macular degeneration [74]. It seems that the activation of inflammasomes is involved in the crosstalk between ER stress and inflammatory responses in some diseases [72,73]. Given its role as an alarming mechanism, ER stress stimulates the secretion of chemokines and cytokines which subsequently recruit immune cells into tissues and activate their inflammatory function [75].…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
“…Myeloma cells treated with D089 also produced higher levels of reactive oxygen species (ROS) and experienced disruption of their mitochondrial membrane potential, additional hallmarks of ER stress. The convergence of ER signals can result in both the activation of inflammasomes [ 27 , 35 , 60 , 61 , 62 , 63 ] and the upregulation of DDIT3 which encodes C/EBP homologous protein (CHOP), a transcription factor which commits the cell to PCD [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later studies revealed that the ER expansion occurs concomitantly with cytoskeleton modifications and subsequent cell size increase [ 219 , 224 ], once again reflecting the interplay between different cellular components. Importantly, convincing findings have also shown that ER stress can prompt inflammatory responses in several age-associated diseases, including atherosclerosis [ 225 ]. In particular, the incidence of chronic endothelial ER stress and activation of the UPR have been demonstrated in vivo at arterial sites susceptible to atherosclerosis [ 226 ].…”
Section: Cellular Organelles In Senescent Cellsmentioning
confidence: 99%